Comparative Proteomic Analysis of Three Chinese Hamster Ovary (CHO) Host Cells - Xu, Ningning (Biochemical engineering journal, 2017)
Chinese hamster ovary (CHO) cells have been widely used to express heterologous genes and produce therapeutic proteins in biopharmaceutical industry. Different CHO host cells have distinct cell growth rates and protein expression characteristics. In this study, the expression of about 1,307 host proteins in three sublines, i.e. CHO K1, CHO S and CHO/dihydrofolate reductase (dhfr)- , were investigated and compared using proteomic analysis. The proteins involved in cell growth, glycolysis, tricarboxylic acid cycle, transcription, translation and glycosylation were quantitated using Liquid chromatography tandem-mass spectrometry (LC-MS/MS). The key host cell proteins that regulate the kinetics of cell growth and the magnitude of protein expression levels were identified. Furthermore, several rational cell engineering strategies on how to combine the desired features of fast cell growth and efficient production of therapeutic proteins into one new super CHO host cell have been proposed